Evolutionary History of the Toll-Like Receptor Gene Family across Vertebrates. (4th December 2019) - Liu, Guangshuai; Zhang, Huanxin; Zhao, Chao; Zhang, Honghai
Abstract: Adaptation to a wide range of pathogenic environments is a major aspect of the ecological adaptations of vertebrates during evolution. Toll-like receptors (TLRs) are ancient membrane-bound sensors in animals and are best known for their roles in detecting and defense against invading pathogenic microorganisms. To understand the evolutionary history of the vertebrate TLR gene family, we first traced the origin of single-cysteine cluster TLRs that share the same protein architecture with vertebrate TLRs in early-branching animals and then analyzed all members of the TLR family in over 200 species covering all major vertebrate clades. Our results indicate that although the emergence of single-cysteine cluster TLRs predates the separation of bilaterians and cnidarians, most vertebrate TLR members originated shortly after vertebrate emergence. Phylogenetic analyses divided 1, 726 vertebrate TLRs into 8 subfamilies, and TLR3 may represent the most ancient subfamily that emerged before the branching of deuterostomes. Our analysis reveals that purifying selection predominated in the evolution of all vertebrate TLRs, with mean d N /d S ( ω ) values ranging from 0.082 for TLR21 in birds to 0.434 for TLR11 in mammals. However, we did observe patterns of positive selection acting on specific codons (527 of 60, 294 codons across all vertebrate TLRs, 8.7‰), which are significantly concentrated in ligand-binding extracellular domains and suggest host–pathogen coevolutionary interactions. Additionally, we found stronger positive selection acting on nonviral compared with viral TLRs, indicating the more essential nonredundant function of viral TLRs in host immunity. Taken together, our findings provide comprehensive insight into the complex evolutionary processes of the vertebrate TLR gene family, involving gene duplication, pseudogenization, purification, and positive selection.